HISTORY TEACHERS' PERCEPTIONS OF DEEP LEARNING APPROACHES: A CASE STUDY OF HISTORY LEARNING AT SMA NEGERI 3 PAMEKASAN - Maulana Fariqi Nuri; Aditya Nugroho Widiadi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to examine the perception of history teachers towards the deep learning approach in history learning at SMA Negeri 3 Pamekasan and analyze the suitability between teachers' perceptions and classroom learning practices. This study uses a qualitative approach with a case study design. Research data was obtained through interviews, learning observations, and document analysis in the form of teaching modules. Data analysis is carried out through the stages of data condensation, data presentation, and conclusion drawing and verification, while the validity of the data is tested through triangulation techniques. The results of the study show that history teachers have a positive perception of the deep learning approach. Teachers view history learning not only as a process of mastering facts, figures, and chronology of events, but as a process that encourages learning awareness, meaningful understanding, and fun learning experiences through the principles of mindful learning, meaningful learning, and joyful learning. This perception has been reflected in the planning and implementation of learning through the use of collaborative strategies, learning media, contextual activities, and reflection activities. However, the implementation of deep learning is still in the development stage because learning is more oriented towards increasing student involvement than developing historical thinking skills in depth. This research shows that teachers' positive perceptions are an important foundation in the application of deep learning, but strengthening pedagogical competence is needed so that history learning is able to develop students' analytical skills, interpretation, and critical reflection.